Generic switching: Do future physicians in Jordan have enough knowledge and a positive attitude? - Al Zoubi, Sura; Gharaibeh, Lobna; Al-Masri, Batool; Alsahele, Ahmad B.; AL-Masaeid, Buthainah (Frontiers in Pharmacology, 2022)
Background: Generic switching is a policy that has shown success in minimising pharmaceutical costs. It has also been used to mitigate recurrent and sudden drug shortages. Not all countries have policies that allow pharmacists to switch to generic drugs independently. In Jordan, only pharmacists at Ministry of Health hospitals automatically switch to generics if doctors had not already done INN prescribing. Objectives: This study targeted medical students to assess their experience with generic switching as patients, their knowledge of the subject as students, and their attitude towards it as future prescribers and policymakers. Methods: This is a descriptive, cross-sectional study conducted online. Eligibility criteria were being a fourth, fifth, or sixth-year medical school student enrolled at any of the six Jordanian universities. The questionnaire was developed by the researchers after a careful review of the relevant literature. Results: Three hundred and ninety students responded to the online questionnaire. Most participants were females (244, 62.6%), senior students in their final (6th) year (162, 41.5%) and with very good academic achievement (166, 42.6%). The highest knowledge scores concerned patient rights (0.73/1.00), followed by knowledge about monitoring after generic switching (0.66/1.00), and patients with known drug allergies (0.66/1.00). Almost half of the participants believe that pharmacists should not be given the right to do generic switching and only 16% stated that they would choose generic drugs if they needed treatment in the future. Multivariate linear regression analysis showed that significant predictors of knowledge were gender, GPA, and family income. No correlations were found between participants’ knowledge scores and their attitudes towards giving pharmacists the right to independently switch drugs, or whether they would accept a substitute from pharmacists rather than having to refer to the physician. Conclusion: Medical students in Jordan lack sufficient knowledge about generic switching. Students need to be more aware of the current policies and regulations of this practice, and the role of each healthcare worker involved in it. They also need to have a more positive attitude toward generic drugs and generic switching practice to facilitate its future implementation.